A Study on the Financials Aspects of Indian Cement Industry - Tejal Dilipbhai Kodiyatar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The growth of infrastructure and building projects depend heavily on the cement industry, which is a key component of the Indian economy. The profitability of the cement industry in India during the previous ten years is thoroughly compared in this study report. The research seeks to offer insightful information about the financial performance of significant participants in this industry and the variables affecting their profitability. The study uses a multidimensional method to evaluate profitability, considering important financial metrics including return on equity, return on assets, net profit margins, and earnings per share (EPS). The research investigates the financial statements of significant cement businesses in India in order to deepen the analysis by taking regional variances and market variables into account. The report also looks at the factors that affect profitability in the Indian cement sector. To determine their influence on profitability trends, a variety of factors are examined, including capacity utilization, pricing tactics, raw material costs, technical improvements, and governmental regulations. The research also examines the industry's competitive environment, considering market share trends and their connection to profitability. Data for this study was obtained between 2010 and 2020 from publicly available financial reports, trade journals, and government sources. The report uses both quantitative and qualitative methodologies and provides a comprehensive assessment of India's cement industry's financial health. The study paper's results help stakeholders in the sector, investors, politicians, and researchers better understand the factors that influence the profitability of the cement business in India. Additionally, it illuminates the industry's resiliency and adaptation in the face of monetary difficulties and global unpredictability, providing important lessons for long-term sustainable growth and development.